Diagnostic challenges with intraoral myeloid sarcoma: report of two cases & review of world literature (Experimental Oncology, 2017)
Background: Myeloid sarcomas (MS) are rare extramedullary tumors composed of blasts of myeloid lineage that either precede, follow or present concomitantly with acute myeloid leukaemia (AML) or myeloproliferative neoplasms. The diagnosis of MS is especially challenging in patients without an antecedent history of leukemia. Methods: We present 2 cases of intraoral MS that presented as de novo lesions. A detailed review of cases of intraoral MS that either preceded or presented along with leukemia has been done with emphasis on diagnostic criteria used. Results: Two male patients aged 28 and 5 years presented with MS with one patient presenting with concomitant AML. A combination of morphological and immunohistochemical methods was used for diagnosis. A thorough review of world literature revealed 44 cases of intraoral MS that presented as de novo lesions. Conclusion: Intraoral MS is a rare tumor with poor prognosis. It may be diagnostically challenging due to its protean clinical manifestations and histological overlap with other tumors.